Sex moderates the relationship between resting heart rate variability and self-reported difficulties in emotion regulation - Williams, DeWayne P.; Koenig, Julian (Emotion, 2019)
Lower resting vagally mediated heart rate variability (HRV) is thought to reflect poorer function of the neurophysiological pathways underlying emotion regulation (ER) and thus, poorer ER abilities. Sex differences in resting HRV exists such that women typically exhibit higher resting HRV than men. It is proposed that greater HRV in women reflects compensation for greater negative affect such as anxiety and depression. However, research has not yet investigated how the association between resting HRV and every day perceived difficulties in ER may be moderated by sex. The current study sought to test this in a sample of 362 young participants (207 females, mean age of 19). Resting HRV was assessed during a 5-min baseline period using an electrocardiogram. Participants then completed the 36-item Difficulties in Emotion Regulation Scale (DERS) designed to evaluate participant's daily difficulties in ER. Controlling for several covariates, sex significantly moderated the relationship between resting HRV and ER difficulties, such that women showed a much stronger relationship compared with men. Specifically, women with lower HRV reported greater difficulties in ER compared with men with lower HRV, whereas women with higher HRV reported slightly lesser difficulties in ER compared with all men. Overall, this study supports a deeper understanding of how neurophysiological differences in ER between men and women-as indexed by resting HRV-may contribute to how effectively individuals regulate their emotions on a day-to-day basis, with implications for well-being.